2009
DOI: 10.1111/j.1365-2702.2008.02405.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of informal caregivers’ needs in providing home‐based end‐of‐life care to people with cancer

Abstract: Enhanced access to professional advice represents a potentially effective method of increasing carers' confidence in their ability to undertake practical aspects of home-based care. Evidence suggests that nurses and other health providers may better assist home-based carers by providing the information and skills-training necessary to facilitate this. This may necessitate the involvement of carers in the design and testing of new educational interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
259
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(274 citation statements)
references
References 46 publications
11
259
0
4
Order By: Relevance
“…Although achieving optimal symptom control is challenging in the hospital, ensuring that the patient will be comfortable after hospital discharge, often in the care of untrained family members, is even more challenging. 16,17 Our study suggests that PCTs have to address this transitional gap. However, there are several systemic barriers.…”
Section: Discussionmentioning
confidence: 88%
“…Although achieving optimal symptom control is challenging in the hospital, ensuring that the patient will be comfortable after hospital discharge, often in the care of untrained family members, is even more challenging. 16,17 Our study suggests that PCTs have to address this transitional gap. However, there are several systemic barriers.…”
Section: Discussionmentioning
confidence: 88%
“…Notwithstanding potential benefits attained from caregiving such as the strengthening their relationship with the patient, the development of new skills, and spiritual growth 8 , and an increased appreciation for life, 9 family caregivers engage in care that may be financially costly, time consuming, physically demanding, and stigma inducing, and that usually impacts negatively on their ability to engage in social and recreational activities. [10][11][12][13] Needs include practical information, 14 emotional support, 15 economic assistance and housing support, 13 improved coordination of formal care and allied services, 16 and bereavement support, 17 while outcomes when engaging in care may include symptoms of psychiatric morbidity 18 and psychological distress; 19 these needs remain largely unmet by services. 20 Despite the practical relevance for providing supports and services to family caregivers, pre-and post-bereavement, the effect of caregiving on bereavement is less clear.…”
Section: Prioritiesmentioning
confidence: 99%
“…41 Carers' willingness to continue in the caring role needs to be constantly reassessed, given that some people have indicated that they are reluctant to be in the role. 10 Ultimately, how can unwillingness to care again be minimized?…”
Section: Implications For Clinicians and Policymakersmentioning
confidence: 99%